Pelatihan Peningkatan Kualitas Produk dan Kemasan Produk di Kelompok Tani Desa Lembah Sari Rumbai Pekanbaru - Sri Maryanti; Yulina Eliza (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this PKM activity is for the resulting product to have a wider market, so that the Product has a brand and pirt permit so that it can be marketed to the supermarket, so that the resulting product has an elegant packaging and attracts consumers to buy the product and the resulting product has a better quality is not easily musty, oily and melempem. The methods used are superstition, training, mentoring and evaluation. From the results of this activity obtained the quality of the product no longer smells musty, not greasy and does not melt because it uses a spiner machine and impulse sealer. PKM partners already have packaging and brand products and household industrial products (PIRT) numbers so that products can have a wider market, one of which is supermarkets. To be able to obtain pirt number PKM partners must follow the training conducted by the Pekanbaru Health Office. Participants will get a certificate of counseling and then for health center.